Non-invasive Imaging in Patients With Chronic Total Occlusions of the Coronary Arteries—What Does the Interventionalist Need for Success? - Kersten, Johannes; Eberhardt, Nina; Prasad, Vikas; Keßler, Mirjam; Markovic, Sinisa; Mörike, Johannes; Nita, Nicoleta; Stephan, Tilman; Tadic, Marijana; Tesfay, Temsgen; Rottbauer, Wolfgang; Buckert, Dominik (Frontiers in Cardiovascular Medicine, 2021)
Chronic total occlusion (CTO) of coronary arteries is a common finding in patients with known or suspected coronary artery disease (CAD). Although tremendous advances have been made in the interventional treatment of CTOs over the past decade, correct patient selection remains an important parameter for achieving optimal results. Noninvasive imaging can make a valuable contribution. Ischemia and viability, two major factors in this regard, can be displayed using echocardiography, single-photon emission tomography, positron emission tomography, computed tomography, and cardiac magnetic resonance imaging. Each has its own strengths and weaknesses. Although most have been studied in patients with CAD in general, there is an increasing number of studies with positive preselectional factors for patients with CTOs. The aim of this review is to provide a structured overview of the current state of pre-interventional imaging for CTOs.